DESAIN TATA KELOLA REKAM MEDIS DALAM SISTEM PELAPORAN PASIEN HEMODIALISA DENGAN METODE WATERFALL STUDI KASUS RSUD AL-IHSAN - Rosdiana Lay Here; Falaah Abdussalaam; Irda Sari (Media Bina Ilmiah, 2023)
Information systems technology is currently growing rapidly; its use has penetrated into various fields, including the health sector. AL-Ihsan Hospital is one of the hospitals that provides services for patients with kidney disorders or hemodialysis. Because at this hospital the management of patient reports is still done manually, it is necessary to design an accurate application in order to obtain hemodialysis patient reports that can be integrated quickly, precisely, effectively, and efficiently. This electronic application is specifically designed for hemodialysis installations. The use of visual basic information technology in medical management with the aim of assisting health workers in collecting data for the reporting process The research method used is a qualitative descriptive method in which data collection is in the form of observation, interviews, and literature study and uses a system development method, namely the waterfall method. This information system is specifically designed for hemodialysis patients, which will make it easier for registration officers, and besides that, it will be very easy for officers to make daily, monthly, and yearly reports using the system that has been created.